2003
DOI: 10.1034/j.1399-0039.2003.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the HLA‐A2403 specificity

Abstract: We found HLA-A*2423 in a subject possessing the HLA-A2403 specificity. Consequently we delineated the A*24 alleles of 41 subjects previously assigned as 'A2403' by serology and/or 'low-resolution' PCR-SSP (allele group: A*2403/10/18/22/23/33) and found that 36 were A*2403, 3 were A*2410 and 2 were A*2433. The A*2410 and A*2433 subjects also typed as A2403. Several likely A*2410/23/33-bearing haplotypes were identified and the frequency of the A*2403/10/18/22/23/33 alleles was determined in 26,826 Welsh blood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A2403ϫ3, short A24 with most A3 and A9 reactive [26] A*2610 A26 A10 ------A26 short A26, A10var A*2611N not expressed Null ------NT A*2612 A26 ---1 A26 (100) b --A26 A*2613 A26 -------A10 NN: A26 A*2614 A26 -------A26 (Continued) …”
Section: International Cell Exchange Uclamentioning
confidence: 96%
“…A2403ϫ3, short A24 with most A3 and A9 reactive [26] A*2610 A26 A10 ------A26 short A26, A10var A*2611N not expressed Null ------NT A*2612 A26 ---1 A26 (100) b --A26 A*2613 A26 -------A10 NN: A26 A*2614 A26 -------A26 (Continued) …”
Section: International Cell Exchange Uclamentioning
confidence: 96%
“…For example, the HLA-A alleles assigned to the A2403 specificity: HLA-A * 2403/2410/2433 were differentiated from HLA-A alleles assigned to the A24 specificity by primer mixture 6 ( Table 3) (see also Street et al, 2003).…”
Section: Differentiation Of Hla Split Specificitiesmentioning
confidence: 99%
“…Inspection of HLA‐A9 epitopes (2, 3) indicated that the A*2312 product should react serologically as a normal HLA‐A23.…”
Section: Detection Human Leukocyte Antigen (Hla)‐a*2312 By Polymerasementioning
confidence: 99%